Perforated Appendicitis in a Neonate Presenting with Intestinal Obstruction - Pierrot Sarkis (EL-Med-Pub, 2013)
We report a case of neonatal perforated appendicitis presenting with an early picture of intestinal obstruction secondary to entrapment of small bowel under inflamed appendix vermiformis.